Comorbidities, Cardiovascular Therapies, and COVID-19 Mortality: A Nationwide, Italian Observational Study (ItaliCO) - Polverino, Francesca; Stern, Debra A.; Ruocco, Gaetano; Balestro, Elisabetta; Bassetti, Matteo; Candelli, Marcello; Cirillo, Bruno; Contoli, Marco; Corsico, Angelo; D'Amico, Filippo; D'Elia, Emilia; Falco, Giuseppe; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: Italy has one of the world’s oldest populations, and suffered one the highest death tolls from Coronavirus disease 2019 (COVID-19). Older people with cardiovascular diseases (CVDs), and in particular hypertension, are at higher risk of hospitalization and death for COVID-19. Whether hypertension medications may increase the risk for death in older COVID 19 inpatients at the highest risk for the disease is currently unknown. Methods: Data from 5625 COVID-19 inpatients were manually extracted from medical charts from 61 hospitals across Italy. From the initial 5625 patients, 3179 were included in the study as they were either discharged or deceased at the time of the data analysis. Primary outcome was inpatient death or recovery. Mixed effects logistic regression models were adjusted for sex, age, and number of comorbidities, with a random effect for site. Results: A large proportion of participating inpatients were ≥65 years old (58%), male (68%), non-smokers (93%) with comorbidities (66%). Each additional comorbidity increased the risk of death by 35% (adjOR=1.35 (1.2, 1.5) p<0.001). Use of ACE inhibitors, ARBs, beta-blockers or Ca-antagonists was not associated with significantly increased risk of death. There was a marginal negative association between ARB use and death, and a marginal positive association between diuretic use and death. Conclusions: This Italian nationwide observational study of COVID-19 inpatients, the majority of which ≥65 years old, indicates that there is a linear direct relationship between the number of comorbidities and the risk of death. Among CVDs, hypertension and pre-existing cardiomyopathy were significantly associated with risk of death. The use of hypertension medications reported to be safe in younger cohorts, do not contribute significantly to increased COVID-19 related deaths in an older population that suffered one of the highest death tolls worldwide.